INFORMATION AND SMALL AND MEDIUM SIZED ENTERPRISES: THE CONVERGENCE OF SHAREDTIME WORK AND INFORMATION AND COMMUNICATION TECHNOLOGIES - Marc-André VILETTE (Management & Marketing)
The subject of this communication is to analyze points of similarities of usingInformation and Communication Technologies (ICT) and Shared Time Work(STW), for a special category of firms, whose place seems to be more andmore important: Small and Middle sized Enterprises (SMEs). After severalparticularities (apart from the size), we will remind their difficulties in HumanResources Management, especially about ICT, then the opportunity in theusing of STW, for research teachers, professionals and media. We willpresent different legal shapes, then precise points of similarities between TICand STW, and finally, results among different kinds of players in this one, inan exploring research.